Prehypertensive State, Mild Hypertension, Metabolic Syndrome and Cardiovascular Risk Factors among Young Adults in Rural Malaysia - Aszrin, Abdullah; Azarisman, Shah M; Jamaluddin , Rahman A; Tariq , Razak A; Noriah, Noor M (IIUM Medical Journal Malaysia, 2018)
Introduction: Prehypertension precedes overt hypertension and has been acknowledged by many guidelines. Hypertension is an important risk factor for cardiovascular disease in Malaysia. Hypertension prevalence is at 42.6% and population-based control is poor at 26.8%. The objective of the study is to ascertain the cardiovascular risk profile of prehypertensive and mildly hypertensive young adults against age-matched controls in rural Malaysia. Methods: 484 (four hundred and eighty four) subjects attending primary care clinic were screened. 91 (Ninety one) young adults with pre/mild hypertension and normotensive, agematched controls were enrolled. The blood pressure and biochemical profiles for both groups were assessed and compared. Results: Fifty-four subjects and 37 controls were enrolled. Amongst subjects, 46.3% had prehypertension and 53.7% had mild hypertension. Mean values compared to age-matched controls for MAP were 102.68 ± 7.48 vs 83.25 ± 6.08 mmHg (p< 0.001), LDL 3.75 ± 0.95 vs 3.32 ± 0.93 mmol/L (p=0.03), FBG 4.65 ± 0.54 vs 4.33 ± 0.42 mmol/L (p=0.03), BMI 28.81 ± 5.16 vs 24.12 ± 4.91 (p< 0.001). The mean BP was significantly associated with BMI, FBG, triglycerides, HDL and the TC/HDL ratio. Conclusions: Greater BMI, FBG, HDL, triglyceride levels and TC/HDL ratio characterised the young adults with pre/mild hypertension. The data suggests that hypertension in young adults is secondary to metabolic syndrome.